Successes, challenges and needs regarding rural health medical education in continental Central America: a literature review and narrative synthesis - Colon-Gonzalez, Maria; El Rayess, Fadya; Guevara, Sara; Anandarajah, Gowri (Rural and remote health, 2015)
Central American countries, like many others, face a shortage of rural health physicians. Most medical schools in this region are located in urban areas and focus on tertiary care training rather than on community health or primary care, which are better suited for rural practice. However, many countries require young physicians to do community service in rural communities to address healthcare provider shortages. This study aimed to: (a) synthesize what is known about the current state of medical education preparing physicians for rural practice in this region, and (b) identify common needs, challenges and opportunities for improving medical education in this area. A comprehensive literature review was conducted between December 2013 and May 2014. The stepwise, reproducible search process included English and Spanish language resources from both data-based web search engines (PubMed, Web of Science/Web of Knowledge, ERIC and Google Scholar) and the grey literature. Search criteria included MeSH terms: 'medical education', 'rural health', 'primary care', 'community medicine', 'social service', in conjunction with 'Central America', 'Latin America', 'Mexico', 'Guatemala', 'Belize', 'El Salvador', 'Nicaragua', 'Honduras', 'Costa Rica' and 'Panama'. Articles were included in the review if they (1) were published after 1984; (2) focused on medical education for rural health, primary care, community health; and (3) involved the countries of interest. A narrative synthesis of the content of resources meeting inclusion criteria was done using qualitative research methods to identify common themes pertaining to the study goals. The search revealed 20 resources that met inclusion criteria. Only four of the 20 were research articles; therefore, information about this subject was primarily derived from expert opinion. Thematic analysis revealed the historical existence of several innovative programs that directly address rural medicine training needs, suggesting that expertise is present in this region. However, numerous challenges limit sustainability or expansion of successful programs. Common challenges include: (a) physicians' exposure to rural medicine primarily takes place during social service commitment time, rather than during formal medical training; (b) innovative educational programs are often not sustainable due to financial and leadership challenges; (c) the majority of physician manpower is in urban areas, resulting in few rural physician role models and teachers; and (d) there is insufficient collaboration to establish clinical and educational systems to meet rural health needs. Recurring suggestions for curricular changes include: (a) making primary care training a core component of medical school education; and (b) expanding medical school curricula in cross-cultural communication and social determinants of disease. Suggestions for health system changes include: (a) improving living and working conditions for rural physicians; and (b) establishing partnerships between educational, governmental and non-governmental organizations and rural community leadership, to promote rural health training and systems. Expertise in rural medicine and training exists in continental Central America. However, there are numerous challenges to improving medical education to meet the needs of rural communities. Overcoming these challenges will require creative solutions, new partnerships, and evaluation and dissemination of successful educational programs. There is a great need for further research on this topic.